Context-based Project Management - Alsaig, Ammar; Alsaig, Alaa; Mohammad, Mubarak (EAI Endorsed Transactions on Context-aware Systems and Applications, 2017)
Context-based computing has become an integral part of the software infrastructure of modern society. Better software are made adaptive to suit the surrounding environment. Context-based applications best fit into environments that undergo constant and frequent changes. Temperature management, Time management, GPS are just few examples where context-awareness becomes inevitable. Project Management is another domain that requires constant monitoring. The current tools of project management handle data gathering, plotting, and organizing, but requires high-level of human intervention to analyze data and integrate it. To the extent of our knowledge there is no efforts to introduce context awareness to project management domain. In this work, we introduce context and formally model project context using FCA. Additionally, we provide the results of the full implementation of our approach on a real-world software project. We show that our approach can formally answer queries that traditional tools could not answer. Also, we introduce a brief comparison between our approach and traditional project management software. Finally, we show that our approach can improve project management tools and minimize the effort spent by project managers.